High Efficacy Rates with Grazoprevir Plus Elbasvir in HCV Monoinfection and HCV/HIV Coinfection - Rizzo, Toni (MD Conference Express, 2014)
Grazoprevir is a highly potent hepatitis C virus (HCV)-specific NS3/4A protease inhibitor. Part A of a Study of the Combination Regimen Grazoprevir (MK-5172) and Elbasvir (MK-8742) ± Ribavirin in Participants With Chronic Hepatitis C [C-WORTHy; NCT01717326] reported efficacy of 89% to 100% in treatment-naïve noncirrhotic patients with HCV genotype-1 infection. This article discusses the expanded C-WORTHy Part B, which assessed the efficacy and safety of grazoprevir plus elbasvir with or without ribavirin in patients with HCV monoinfection and patients with HCV and human immunodeficiency virus coinfection.